2020
DOI: 10.14715/cmb/2020.66.4.29
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diarrheal activities of phytol along with its possible mechanism of action through in-vivo and in-silico models

Abstract: Phytol (PHY), a chlorophyll-derived diterpenoid, exhibits numerous pharmacological properties, including antioxidant, antimicrobial, and anticancer activities. This study evaluates the anti-diarrheal effect of phytol (PHY) along with its possible mechanism of action through in-vivo and in-silico models. The effect of PHY was investigated on castor oil-induced diarrhea in Swiss mice by using prazosin, propranolol, loperamide, and nifedipine as standards with or without PHY.PHY at 50 mg/kg (p.o.) and all other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the current work, three phytocompounds were screened from the V. canescens plant's µOR and δOR antidiarrheal inhibitory properties. Diarrhea is reduced when mu-and delta-opioid receptors are targeted [18,19]. In order to identify prospective antidiarrheal inhibitors, specifically against µOR and δOR enzymes, a total of three phytochemicals were chosen and virtually screened by molecular docking, MD, and drug-likeness/ADMET assays.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, three phytocompounds were screened from the V. canescens plant's µOR and δOR antidiarrheal inhibitory properties. Diarrhea is reduced when mu-and delta-opioid receptors are targeted [18,19]. In order to identify prospective antidiarrheal inhibitors, specifically against µOR and δOR enzymes, a total of three phytochemicals were chosen and virtually screened by molecular docking, MD, and drug-likeness/ADMET assays.…”
Section: Discussionmentioning
confidence: 99%
“…Loperamide is a synthetic piperidine moiety-based opioid that binds to intestinal mu-opiate receptors (μORs) . Targeting mu- and delta-opioid receptors leads to inhibition of diarrhea. , Hence, we performed docking simulations on μOR and δOR. We have performed docking simulations using MOE (2016.0802).…”
Section: Discussionmentioning
confidence: 99%
“…27 Targeting mu-and delta-opioid receptors leads to inhibition of diarrhea. 28,29 Hence, we performed docking simulations on μOR and δOR. We have performed docking simulations using MOE (2016.0802).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can be used as a precursor for the manufacture of synthetic forms of vitamin E and vitamin K [15]. Interestingly, it has been reported to possess various pharmacological properties, including anti-inflammatory [16,17], anti-diarrheal activities [18], antinociceptive, antioxidant [19], and anti-diabetic [20], activities. In addition, other predominant compound found in this study, such as n-Hexadecanoic acid or Palmitic acid (CH3 (CH 2) 14COOH), a saturated fatty acid is an anti-inflammatory compound as it is found to exert anti-inflammatory effect by inhibiting phospholipase A2 (PLA 2 plays crucial roles in diverse cellular responses, host defense, and signal transduction) [21].…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Furthermore, Yosboonruang et al [1], reported that S. neglecta possesses anti-inflammatory activity by reducing the release of TNF-α from macrophages. Phytol exhibits anti-inflammatory activity, possibly via COX-1 and 2, NF-κB, and IL-1β dependent pathways [18], and attenuates the inflammatory response by inhibiting neutrophil migration that is partly caused by reduction in IL-1b and TNF-a levels and oxidative stress [17]. In this study, Phytol was found to be higher in the methanol extract than that in the propylene glycol extract, but the propylene glycol extract inhibited NO production higher than the methanol extract did.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%